Pengujian Validitas Indonesian Academic Resilience Scale pada Mahasiswa (Jurnal Ilmiah Psikologi MIND SET, 2024)
The Indonesian Academic Resilience Scale developed by Ramdani, et al. (2020) has demonstrated good validity evidence in measuring academic resilience among school student groups. This study aims to complement the validity evidence of this measurement tool in a university student population. The sample in this study consisted of active students from a university in Jakarta (n=200). Validity evidence was assessed using confirmatory factor analysis (CFA) techniques and correlations with other measurement tools. The CFA results showed that the item factor loadings ranged from 0.52 to 0.83. Reliability was assessed using internal consistency reliability (α = 0.476 – 0.778). The test results indicated that adjustments to the measurement tool are needed for use with university students, retaining only 16 out of 27 items.